PELATIHAN SADARI MENINGKATKAN PENGETAHUAN WANITA MENOPAUSE TENTANG SADARI SEBAGAI CARA DETEKSI DINI KANKER PAYUDARA - Sumarni Sumarni; Hartati Hartati; Afiyah Sri Harnany (Poltekkes Kemenkes Semarang, 2021)
Menopause is a normal change that occurs in a woman's life when her menstrual period stops. Menopause causes women to be susceptible to cancer, one of which is breast cancer. One way that can be done to detect early incidence of breast cancer is by doing Breast Self-Examination (BSE) routinely, and this requires a woman's knowledge of how to detect breast cancer with the breast self-examination method (BSE). This study used a quasi-experimental study with a pre test - post test design with a control group. The population in this study were all menopausa women (45 - 55 years) in Wates Village, Wonotunggal Subdistrict, Batang Regency. The sampling technique was simple random (simple ramdom). In this study, the sample used was 60 respondents, with a sample size of 30 for the intervention group and 30 samples for the control group. The data analysis used the Wilcoxon test to determine the effect of BSE training, while to determine the difference in knowledge between the intervention group and the control group, the Friedman test was used to test the normality of the data using the Kolmogorov-Smirnov non-parametric statistical test. The results showed that there was an effect of providing BSE training in the intervention group on knowledge with a value of p 0.05.Suggestions are given to increase public awareness, especially menopausal women about breast self-examination (BSE), through health training activities. Keywords: BSE training, menopausal age women, knowledge